STUDENT BUSINESS DYNAMIC: BALANCING STUDY AND BUSINESS - Andi Hajar; Zakiyah Febrina Alasta; Kayla Del Alinan (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
The phenomenon of students running side businesses is increasing in the digital economy era, but this poses challenges in maintaining a balance between academic and business responsibilities. This study aims to analyze the dynamics of role conflict, time management strategies, and the impact of business involvement on the academic performance of students at Universitas Negeri Makassar. The method used is descriptive qualitative with data collection techniques through in-depth interviews, questionnaires, observations, and literature studies. The results show that entrepreneur students, mostly in the third and fourth semesters, manage various businesses such as culinary and creative services, some of which have been started since elementary and junior high school. Field findings revealed that although students have structured schedules with a score of 4 out of 5, they still face the challenge of "difficulty managing time" due to the dual burden and the lack of dispensation from the university. Students overcome these obstacles through strategic prioritization and utilization of digital technology through a techno-entrepreneurship approach. Social support from family and college friends proved to be a crucial factor in maintaining students' emotional stability. In conclusion, the motivation for financial independence encourages students to remain consistent in carrying out dual roles despite having to face psychological pressures and limited energy in daily life.